The Environmental Pollutant Bromophenols Interfere With Sulfotransferase That Mediates Endocrine Hormones - Dai, Zhihong; Zhao, Furong; Li, Ying; Xu, Jing; Liu, Zhiyu (Frontiers in Endocrinology, 2022)
Bromophenols (BPs), known as an important environmental contaminant, can cause endocrine disruption and other chronic toxicity. The study aimed to investigate the potential inhibitory capability of BPs on four human sulfotransferase isoforms (SULT1A1, SULT1A3, SULT1B1 and SULT1E1) and interpret how to interfere with endocrine hormone metabolism. P-nitrophenol(PNP) was utilized as a nonselective probe substrate, and recombinant SULT isoforms were utilized as the enzyme resources. PNP and its metabolite PNP-sulfate were analyzed using a UPLC-UV detecting system. SULT1A1 and SULT1B1 were demonstrated to be the most vulnerable SULT isoforms towards BPs' inhibition. To determine the inhibition kinetics, 2,4,6-TBP and SULT1A3 were selected as the representative BPs and SULT isoform respectively. The competitive inhibition of 2,4,6-TBP on SULT1A3. The fitting equation was y=90.065x+1466.7, and the inhibition kinetic parameter (Ki) was 16.28 µM. In vitro-in vivo extrapolation (IVIVE) showed that the threshold concentration of 2,4,6-TBP to induce inhibition of SULT1A3 was 1.628 µM. In silico docking, the method utilized indicated that more hydrogen bonds formation contributed to the stronger inhibition of 3,5-DBP than 3-BP. In conclusion, our study gave the full description of the inhibition of BPs towards four SULT isoforms, which may provide a new perspective on the toxicity mechanism of BPs and further explain the interference of BPs on endocrine hormone metabolism.